Pollen viability and stigma receptivity in vanilla (Vanilla planifolia Andrews) - Goudra, Y G Shadakshari, D Madaiah, M Dinesh Kumar, K V Shivakumar, K H Bhagavantha (Journal of Spices and Aromatic Crops, 2003)
Pollen viability and stiglna receptivity period before and after complete flower opening was studied by hand pollinating the flowers/flower buds with its own pollen and fresh viable pollen. Based on the results, the pollen viability periods were 23 h before complete flower opening and 16 h 30 min after complete flower opening. The stigma receptivity periods were 41 h before complete flower opening and 17 h after complete flower opening under hill zone conditions.